2021
DOI: 10.1021/acs.chemmater.1c00324
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Per- and Polyfluoroalkyl Substances from Water with Zirconium-Based Metal–Organic Frameworks

Abstract: Per-and polyfluoroalkyl substances (PFASs) are an emerging class of contaminants raising increased levels of concern due to their toxic, bioaccumulative, and persistent nature. Current solutions for removing PFAS from contaminated water rely on adsorption-based methods where commonly used sorbents, for example, activated carbons and ion-exchange resins, exhibit low adsorption capacity and a long equilibration time. Motivated by the generally deficient performance of these current materials, this work addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 48 publications
4
82
0
2
Order By: Relevance
“…This corresponds to the capture of 1.75 PFOA per NDMB group in PAF-1-NDMB (consisting of 0.79 NDMB in 1 g PAF-1-NDMB as illustrated above), thereby implying the great accessibility of PAF-1-NDMB for PFOA. As far as we know, the maximum uptake capacity of PAF-1-NDMB is unprecedented among all adsorbent materials reported thus far for PFOA adsorption, including NU-1000 (507 mg g −1 ) 10 , DFB-CDP (33 mg g −1 ) 16 , MIL-101 (Cr) (460 mg g −1 ) 20 , MWNTs (140 mg g −1 ) 51 , FCX4-P (188.7 mg g −1 ) 52 , UiO-67 (700 mg g −1 ) 53 , AC (52.8 mg g −1 ) 54 , all-silica Beta (β) (371 mg g −1 ) 55 , resins (1500 mg g −1 ) 23 , 56 . Although the PAF-1-NDMB exhibited a BET surface area of only 108 m 2 g −1 , it demonstrated a superior uptake capacity due to the efficacious functionalization.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This corresponds to the capture of 1.75 PFOA per NDMB group in PAF-1-NDMB (consisting of 0.79 NDMB in 1 g PAF-1-NDMB as illustrated above), thereby implying the great accessibility of PAF-1-NDMB for PFOA. As far as we know, the maximum uptake capacity of PAF-1-NDMB is unprecedented among all adsorbent materials reported thus far for PFOA adsorption, including NU-1000 (507 mg g −1 ) 10 , DFB-CDP (33 mg g −1 ) 16 , MIL-101 (Cr) (460 mg g −1 ) 20 , MWNTs (140 mg g −1 ) 51 , FCX4-P (188.7 mg g −1 ) 52 , UiO-67 (700 mg g −1 ) 53 , AC (52.8 mg g −1 ) 54 , all-silica Beta (β) (371 mg g −1 ) 55 , resins (1500 mg g −1 ) 23 , 56 . Although the PAF-1-NDMB exhibited a BET surface area of only 108 m 2 g −1 , it demonstrated a superior uptake capacity due to the efficacious functionalization.…”
Section: Resultsmentioning
confidence: 98%
“…Among various technologies used for PFAS removal from contaminated water such as oxidative 6 , UV irradiation 7 , sonochemical 8 , and electrochemical methods 9 , adsorption is highly favored owing to its simplicity and high efficiency in the purification process of contaminated water 10 . Thus, a wide range of adsorbents have been investigated for PFAS elimination from polluted waters.…”
Section: Introductionmentioning
confidence: 99%
“…Well known in this class are UiO-66, DUT-69, NU-1000, and MOF-808, among others. ,, These MOFs contain a variety of topologies, metal analogues, coordinating ligands, and connectivity, resulting in a broad range of chemical and physical properties. Experimental studies have shown their successful utilization for usage in various applications, such as those previously mentioned. However, a complete theoretical description of the processes involved in these applications is an active area of research, which can be utilized to design the next-generation MOF-based technologies with higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are porous, crystalline materials composed of inorganic nodes and organic linkers that assemble into multidimensional lattices through coordination bonds. The unique characteristics of MOFs such as ultra-high surface areas and pore volumes combined with their structural tunability render them as promising candidates for the adsorption and/or separation of small molecules. Rapid adsorption kinetics are commonly found within such applications, making MOFs particularly promising candidate materials for water remediation. For example, MOFs have been proven to be effective in removing a wide range of pollutants from water including heavy metals, dyes, and pharmaceuticals. ,, However, the application of MOFs for PFAS removal is underexplored . The few existing PFAS@MOF studies focus on the adsorption of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), two well-known long-chain perfluoroalkyl acids (PFAA), but the performance of MOFs on short-chain PFAS is unclear. Furthermore, there are nearly 5000 different types of PFAS and the role of their charge state, chain length, and head group functionality on the adsorption behavior using MOFs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%